Case Report: ECMO-Assisted Uniportal Thoracoscopic Tracheal Tumor Resection and Tracheoplasty: A New Breakthrough Method - Li, Zi-Hao; Dong, Bo; Wu, Chun-Li; Li, Shi-Hao; Wu, Bin; Sheng, Yin-Liang; Li, Feng; Qi, Yu (Frontiers in Surgery, 2022)
Primary tracheal tumors are seldom seen, and most of them are malignant. At present, the main treatment is surgical resection. It is rare to accomplish tracheal tumor resection and tracheoplasty via uniportalal thoracoscopy. In order both to maintain the patient's oxygen supply during surgery and to reduce the size of the surgical incision, we have innovatively integrated the ECMO-assisted and uniportal thoracoscopic techniques for the first time, perfectly achieving tracheal tumor resection and tracheoplasty. The intraoperative manipulation was only 180 min in duration. The patient returned to the intensive care unit and recovered smoothly after the surgery. The patient was discharged from the hospital 17 days after the operation. ECMO-assisted uniportal thoracoscopic tracheal resection and tracheoplasty provides a new idea and method for colleagues.